A redox-switchable catalyst with an 'unplugged' redox tag. Issue 75 (1st September 2022) - Gutiérrez-Peña, Cristian L.; Poyatos, Macarena; Peris, Eduardo
Abstract : A series of bis-(propyl-imidazoliylidene)-napthalenediimide (NDI) complexes of rhodium and iridium showed effective redox-switching properties, despite the electronic disconnection between the NDI moiety and the metal centres. Abstract : Two bis-(propyl-imidazolium)-napthalenediimide (NDI) salts were prepared and used as N-heterocyclic carbene (NHC) precursors for the preparation of dimetallic complexes of rhodium and iridium. Infrared spectroelectrochemical studies indicate that the metals are sensitive to changes in the electronic state of the NDI moiety. The catalytic behavior of the rhodium and iridium complexes was tested in the cycloisomerization of alkynoic acids, where the complexes showed effective redox-switching properties.